THE EFFECT OF USING INDEX CARD MATCH IN TEACHING LEARNING ENGLISH GRAMMAR AT SMP ISLAM AL-AZHAR PEKANBARU - Rhenie Puspita Sari; Rumiri Aruan; Masyhur Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: This study aims to determine whether Index Card Match has an effect in teaching learning simple present tense and simple past tense among the second-grade students of SMP Islam Al-Azhar Pekanbaru, which is consist of 50 students from two classes, where 8A as Experimental Class and 8B as Control Class. This study is conducted by test and questionnaire. In order to determine the result of the test and questionnaire, the Quantitative experimental research is applied in this study. The result of the study shows that: (i) the students' knowledge of the simple present tense and simple past tense improved after applying the Index Card Match strategy; (ii) in the pre-test, the experimental class mean score was 81.1%, compared to 75.1% for the control class. In contrast, the experimental class mean score on the post-test was 94.5%, compared to the control class mean score was 84%; (iii) the results of the test proved that Index Card Match strategy was successful to dicovered the issue in this study.Keywords: Effect, Index Card Match, Grammar, Teaching Learning Process